Management Of Biomedical Waste in Oral Maxillofacial Surgery- A Scoping Review - Dr. Dhanalakshmi P; Dr. Vijay Ebenezer (Revista Electronica de Veterinaria, 2023)
Biomedical waste is nothing but any solid or liquid waste produced during diagnosis, accompanied by its container and any interim product from treatment or vaccination of human beings or animals involved in their research operations. These components have distinctive physiochemical and biological properties, as well as varying levels of toxicity and potential threat, which require for various methods and disposal tactics. The quantity of biomedical waste produced daily rose along with the number of healthcare facilities. Compared to other household or industrial trash, they are very different biomedical wastes that are dangerous and can harm people, animals, or the environment because they can spread viruses to those who touch or come into contact with them, including HIV, Hepatitis B, C, and Tetanus. Because of its hazardous nature, managing it properly is crucial, and it is currently the largest problem. Appropriate treatment techniques must be used to handle these wastes. The Ministry of Environment and Forests released the Bio-Medical Waste Rules, 1998 to govern the appropriate handling and disposal of biomedical wastes. This review article addresses several methods for managing biological waste.